1991
DOI: 10.1210/mend-5-6-836
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Function Analysis of the Rat Prolactin Promoter: Phasing Requirements of Proximal Cell-Specific Elements

Abstract: Expression of PRL, a member of the GH family of genes, is restricted to the lactotroph cells of the anterior pituitary. The proximal promoter of the rat PRL (rPRL) gene contains four factor-binding sites. Three nonadjacent elements, footprints (FP) I, III, and IV, are separated by an integral number of helical turns and bind a pituitary-specific factor, LSF-1. FP II binds another factor present in pituitary and nonpituitary cells. The mechanisms by which DNA-bound proteins influence RNA polymerase-II activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
2

Year Published

1992
1992
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 28 publications
0
10
2
Order By: Relevance
“…Stimulation of the reporter plasmids showed a 10 bp periodicity and changes of only 2 or 3 bp could drastically reduce the degree of co-operativity [46]. DNA-turn-dependent reductions in rat prolactin promoter activity have also been reported for the two proximal elements [47]. In addition, the region of spacing divergence between the human and rat insulin 1 promoters begins only 2 bp upstream of the 6 bp E1 consensus sequence and would, therefore, be within the binding footprint of E47/β2.…”
Section: Discussionmentioning
confidence: 83%
“…Stimulation of the reporter plasmids showed a 10 bp periodicity and changes of only 2 or 3 bp could drastically reduce the degree of co-operativity [46]. DNA-turn-dependent reductions in rat prolactin promoter activity have also been reported for the two proximal elements [47]. In addition, the region of spacing divergence between the human and rat insulin 1 promoters begins only 2 bp upstream of the 6 bp E1 consensus sequence and would, therefore, be within the binding footprint of E47/β2.…”
Section: Discussionmentioning
confidence: 83%
“…To examine the possibility of an Ets‐DNA‐Ets complex formed on the DYT1 Ets direct repeat motif, we tested the effects of increasing the distance between the two Ets cores. Changing the distance between adjacent binding sites in promoters affects the relative position of a core sequence on the DNA turn as well as their relative distance along the DNA helix, resulting in decreased promoter activity in the majority of genes (Harvey et al. 1991; Baillat et al.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that GHF-1 alone does not mediate the Ras/Raf activation of the rPRL promoter. However, examination of the rPRL promoter DNA sequence reveals that the EBS at Ϫ217 to Ϫ209 is immediately adjacent to FPIV, the most distal and lowest-affinity GHF-1-binding site (28) (Fig. 2B), suggesting that deletion at Ϫ212 not only destroys the EBS but, by doing so, also interferes with a composite c-Ets-1/GHF-1 Ras/Raf-responsive element.…”
Section: Ghf-1 But Not Ghf-2 Synergistically Enhances Ras and Raf Actmentioning
confidence: 99%